2020
DOI: 10.1177/0951484820943600
|View full text |Cite
|
Sign up to set email alerts
|

Employee involvement in innovation activities in hospitals: How perception matters

Abstract: Employees are a very important source of innovation and essential for the generation, dissemination and implementation of these ideas throughout the organization. This is especially relevant when considering innovation in services during service (co-) creation such as within the healthcare sector. However, perceived employee involvement in innovation (EII) and between stakeholder group interactions in hospitals has not yet been studied in detail. This paper addresses the following research questions: “How do d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…In this regard, the current research study argues that employees are an important source in providing innovative solutions in an organization and, hence, seeking to enhance EIB in healthcare organizations is not without logic. This importance of employees as a source of innovation is also supported by extant researchers [38][39][40]. Second, the healthcare sector represents a classic case in which the duration of employee-patient interaction is when as compared to other segments as healthcare employees keep in touch with the patients even for several weeks during their stay in a hospital [41,42].…”
Section: Introductionmentioning
confidence: 90%
“…In this regard, the current research study argues that employees are an important source in providing innovative solutions in an organization and, hence, seeking to enhance EIB in healthcare organizations is not without logic. This importance of employees as a source of innovation is also supported by extant researchers [38][39][40]. Second, the healthcare sector represents a classic case in which the duration of employee-patient interaction is when as compared to other segments as healthcare employees keep in touch with the patients even for several weeks during their stay in a hospital [41,42].…”
Section: Introductionmentioning
confidence: 90%
“…What is understood and managed as falling within or outside public health systems (e.g., aging, socioeconomic vulnerabilities, informal caregiving, and resilient communities) ( Barr et al, 2003 ) may hinder sustainable health system-oriented innovation where the population health, superior care and fair service provision “regardless of age, group identity, or place” should prevail ( Fineberg, 2012 ). Because our sample was comprised of innovators operating both not-for-profits and for-profits, our findings also highlighted how healthcare management receptiveness to diverse forms of entrepreneurship ( Santos et al, 2015 ; Giacomelli et al, 2019 ) could help to “think outside the health system box” ( Busch-Casler et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is compatible with studies indicating that innovation depends upon the quality and thoroughness of the interactions between innovators, health and social care practitioners, and healthcare managers ( Martin et al, 2012 ). Though inclusiveness is aligned with the growing importance attached to health services co-creation, Busch-Casler et al (2020) found that “lower level employees are often left out” of innovation processes at an early stage and this may be due to “top-down” governance. Likewise, our study highlights that the diversity and scope of stakeholder engagement is modulated by power relations affecting how innovators may have access to managers, providers, patients and their caregivers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The leaders of an organization should make a concerted effort to promote employee engagement by offering visible chances for individuals or groups at all levels of the company to have a greater voice (Prieto et al, 2020). When new ideas are generated, disseminated, and implemented in the workplace by employees, they represent an important source of innovation (Busch-Casler et al, 2020). The engagement of the whole firm's employees in improving the working environment, product quality, equipment productivity, and, finally, the competitiveness of the organization is how employee involvement is described by the industry.…”
Section: Employee Involvementmentioning
confidence: 99%